DESCRIPTION OF PHYSICAL ACTIVITY IN HYPERTENSION CLIENTS - Citra Windani Mambang Sari; Via Komalasari; Iwan Suhendar (Journal of Nursing Care, 2021)
Hypertension is a non-communicable disease and has a risk of heart disease. Hypertension can be managed by doing physical activity. Physical activity can control blood pressure in hypertensive clients. The purpose of this research was to identify the overview of the biological activities of hypertensive clients at the Guntur Community Health Centre in Garut Regency.The research type was a quantitative descriptive with the study population of hypertensive patients who were registered at Guntur Community Health Centre. The sampling method in this research was a total sampling method, and the total number of this study was 118 hypertensive patients. This research instrument used the long form of the International Physical Activity Questionnaire with a number of 25 questions and consisted of 4 activity domains. The data were processed using the analysis of distribution frequency and percentage. The results showed as many as 100 respondents (84.7%) did a mild physical activity, and none did moderate physical activity, and as many as 18 respondents (15.3%) did a strenuous physical activity. From the research results, it can be concluded that most of the respondents did a mild physical activity. The implication of this research is to provide health education about appropriate physical activity for hypertensive clients at Guntur Health Center.